Penilaian Kinerja Produk Reksadana dengan Menggunakan Metode Perhitungan Jensen Alpha, Sharpe Ratio, Treynor Ratio, M2, dan Information Ratio - Magdalena Santosa; Amelina Apricia Sjam (Jurnal Manajemen Maranatha, 2012)
This research determined the results of the performance of mutual fund products offered by PTNISP Asset Management with Risk Adjusted Return calculation model. To perform an assessment of the mutual funds, this research analyzed 6 of 8 mutual fund products offered by PT NISP Asset Management during the years 2008 and 2009. The data analysis methods used were Sharpe Ratio, Treynor Ratio, Jensen Ratio, M2 or M-square measure and Information Ratio.The results of the research showed that mutual funds offered by PT NISP Asset Management should be selected by the investor.The results also showed that the performance of all mutual funds offered by PT. NISP Asset Management that were analyzed performed well, but there was only one mutual fund product rated to survive in times of crisis, which was IndeksSahamProgresif. This mutual fundproduct is recommended for investors who are looking to invest in PT. NISP Asset Management.